Solve using any method
Tutors, please sign in to answer this question.
Factor the expression:
x2 +x - 30 = (x+6)(x-5) = 0
(because 6 and -5 are factors of -30 that make 6x - 5x = x - second term)
The product of two terms is zero if both are equal to zero or one of them.
It gives you x+6 = 0 and x-5 = 0 or
x = -6 and x = 5
Check the answer by substituting these numbers back into the expression. Both satisfy.
x2 + x -30 = 0
This expression can be factored into
(x + 6)*(x - 5) = 0
which is true when x = -6 or x = 5.